The Effectiveness of 3D Animation Movie Media in Learning Literature in Junior High School - Nalan Meilia Sisi; Muhammad Fuad; Edi Suyanto; Munaris; Siti Samhati (Global Writing Academica Researching & Publishing, 2023)
The purpose of this research is to develop a 3D animation movie and find out its feasibility and effectiveness in teaching literature in junior high schools. This research is a development-research. The development model adapts Borg and Gall's research and development procedures to the stages of (1) potential and problems; (2) collection of data needs; (3) development through product design and developing initial product forms; (4) product evaluation through validation by relevant experts/experts; (5) revision of the validation product design; (6) peer-to-peer product trials and limited-scale class trials and revisions to the trial results followed by large-scale class trials. Data collection techniques by observation, interviews, and questionnaires at Xaverius Way Halim Middle School Bandar Lampung. The results of the material expert test for the animated movie